2020
DOI: 10.1080/2090598x.2020.1816150
|View full text |Cite
|
Sign up to set email alerts
|

Electro-mediated drug administration of mitomycin C in preventing non-muscle-invasive bladder cancer recurrence and progression after transurethral resection of the bladder tumour in intermediate- and high-risk patients

Abstract: (2020): Electro-mediated drug administration of mitomycin C in preventing non-muscle-invasive bladder cancer recurrence and progression after transurethral resection of the bladder tumour in intermediate-and high-risk patients, Arab Journal of Urology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The largest reported study to date evaluated 124 EMDA/MMC treatments [11-16]. Thus, this research adds to the current literature by describing patient characteristics, efficacy, and recurrence as well as progression outcomes after EMDA/MMC treatments in the largest study reported to date, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The largest reported study to date evaluated 124 EMDA/MMC treatments [11-16]. Thus, this research adds to the current literature by describing patient characteristics, efficacy, and recurrence as well as progression outcomes after EMDA/MMC treatments in the largest study reported to date, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 93%
“…At the end of followup, recurrence-free rates were 75, 71.4, 50, and 25% in TaG3, T1G3, CIS, and TaT1G3 + CIS patients, respectively; progression-free rate was 61%. Carando et al [15,16] reported the data of 65 patients and 112 patients affected by NMIBC that performed a complete TURBT followed by EMDA/MMC. At the end of follow-up, recurrence-free rates were 84 and 75% in 65 and 112 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMDA protocols adopted by the various centers show slight variations, with earlier studies using a lower current amplitude of 15 mA over shorter time periods of 20 min, while most subsequent studies utilize a maximum of 20 to 23 mA of pulsed DC applied over a duration of 30 min [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. No differences in tolerability and adverse side effects were observed with the higher amplitude and longer durations.…”
Section: Pre-clinical Studies and Clinical Applications Of Emda In On...mentioning
confidence: 99%